Taxonomic and functional shifts of gut microbiome in immunoglobulin A vasculitis children and their mothers - Liang, Yijia; Zhao, Changying; Zhao, Lanlan; Sheng, Dashuang; Chen, Bin; Zhao, Guoping; Wang, Qinghua; Zhang, Lei (Frontiers in Pediatrics, 2024)
Objectives: To examine the gut microbiota characteristics in children with immunoglobulin A vasculitis and their interrelationships with the host, while evaluate the vertical inheritance of microbiota in the development and progression of IgA vasculitis. Methods: This study investigated the gut microbiome of 127 IgA vasculitis mother-child pairs and 62 matched healthy mother-child pairs, and compared the gut microbial composition of different groups. The pathway enrichment analysis evaluated potential gut microbiome-mediated pathways involved in the pathophysiology of IgA vasculitis. The Spearman correlation analysis illustrated the relationships between clinical variables and bacterial biomarkers. Results: This study identified distinct intestinal microbiome in IgA vasculitis children compared to healthy children, and further pointed out the association in gut microbiota between IgA vasculitis children's and their mother's. The relative abundance of Megamonas and Lactobacillus in IgAV children was positively correlated with that in their mothers. The pathway enrichment analysis found microbial biosynthesis of vitamins and essential amino acids was upregulated in children with IgA vasculitis. Correlation analysis showed bacterial biomarkers were correlated with indicators of blood coagulation. Conclusion: Children with IgA vasculitis have unique bacterial biomarkers and may affect coagulation function, and their gut microbiome was closely associated with that of their mothers. The observed association in gut microbiota between IgA vasculitis children and their mothers suggested a potential intergenerational influence of the maternal microbiota on the development or progression of IgA vasculitis in children.